Global Land Grab and the Balkans: Continuity and Changes in a Unique Historical Context. Issue 3 (4th May 2018) - Mandacı, Nazif; Tutan, Mehmet Ufuk
Abstract: Current developments concerning land grabs in the Balkans suggest that the region is re-experiencing in the post-socialist era what happened in the seventeenth and eighteenth centuries due to the decline of the Ottoman land tenure system, under identical conditions involving fundamental socio-political transformations and integration with global capitalism. These changes are emblematic of a transfer of common to individual ownership. Nowadays, small landholders in some parts of the region—mainly the former labourers on socialist agricultural cooperatives—are influenced by the accelerating trend of (re)concentrating landownership, which in some cases takes the form of land grabbing similar to that seen in Africa. This study examines the historical continuity between the Ottoman rule over fledgling nation-states and the post-socialist era by referring to widely discussed socio-economic and political developments regarding contemporary land grab processes.